Effect of Moringa oleifera aqueous leaf extract on hepato-renal changes of albino rats induced with Salmonella typhimurium - Suleiman, Nasiru; Ibrahim, Bulama; Ahmed, Bagudo Ibrahim; Zayyanu, Attahiru (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study was designed to evaluate the effect of Moringa oleifera against Salmonella typhimurium infected changes in liver and kidney function parameters in albino rats. Methods: Twenty acclimatized albino rats were divided into four groups of five rats each (groups A-D). Groups B, C and D were exposed to 0.1ml (3.0x104 CFU) of Salmonella typhimurium. Six hours post- infection, Groups B and C were treated with 50 and 100mg/kg of Moringa oleifera aqueous leaf extract respectively and continued for 21 days. Group D was not treated while group A was neither infected nor treated. Serum alkaline phosphatase (ALP), alanine transaminase (ALT), aspartate transaminase (AST), bilirubin, albumin, total protein, urea and creatinine were estimated using standard methods. All data were collected and analyzed in October 2015. Results: S. typhimurium infection significantly (p<0.05) increased the levels of ALP, ALT, AST, bilirubin, urea and creatinine when compared with control levels (Group A). Total protein and albumin concentrations were significantly (p<0.05) reduced following the infection. However, Moringa oleifera supplementation was associated with significant (p<0.05) decrease in the levels of ALP, ALT, AST, bilirubin, urea and creatinine. It is also associated with decrease in concentrations of total protein and albumin. Conclusions: This study showed S. typhimurium infection induced changes in liver and kidney function parameters and also revealed possible amelioratory effects to these changes after Moringa oleifera supplementation.